2003
DOI: 10.1002/bjs.4062
|View full text |Cite
|
Sign up to set email alerts
|

Heat preconditioning prevents oxidative stress-induced damage in the intestine and lung following surgical manipulation

Abstract: This study suggests that mild whole-body hyperthermia before surgery might offer protection from postoperative complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…We have shown previously that mild heat preconditioning protects small intestinal mitochondria and brush border membrane against oxidative stress induced by surgical manipulation (23,24), an effect mediated by upregulation of cellular antioxidants such as superoxide dismutase and catalase (13). Vitamin A and its metabolites have been shown to have protective effects against acute liver damage, hepatic inflammation, and fibrosis in a rat model (25,26).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…We have shown previously that mild heat preconditioning protects small intestinal mitochondria and brush border membrane against oxidative stress induced by surgical manipulation (23,24), an effect mediated by upregulation of cellular antioxidants such as superoxide dismutase and catalase (13). Vitamin A and its metabolites have been shown to have protective effects against acute liver damage, hepatic inflammation, and fibrosis in a rat model (25,26).…”
Section: Discussionmentioning
confidence: 98%
“…Our earlier studies have shown that heat preconditioning can increase the activity of the antioxidant enzymes, superoxide dismutase and catalase, in the intestine (13) and it is known that retinoic acid can induce the transcription of a number of genes (14). This suggests that the mechanism of cytoprotection by heat preconditioning might involve induction of retinoic acid formation, and led to the hypothesis that heat preconditioning would enhance the retinoic acid levels and maintain cell proliferation and differentiation in the intestine.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Hyperthermia has been applied as a common type of PC. Traditional model of hyperthermic PC in rat is 41 °C for 15 min (Huang et al, 2002;Thomas et al, 2003). However, this model would result in more cellular damage.…”
Section: Preconditioning Of the Lung Current Experimental Status Andmentioning
confidence: 99%
“…The detailed mechanisms of PC varies in different animal species or organ systems, although in general these could be classified as the immediate acquisition which is related to post-translational modification, or delayed induction related to new protein synthesis (Kirino, 2002). These "biphasic" phenomena of PC have been observed in brain, heart, and liver tissues in human or other animals (Kirino et al, 1991;Bolli, 2000;Raeburn et al, 2001;Fernán-dez et al, 2002;2003;Harkin et al, 2002;Xia et al, 2003;Thomas et al, 2003). PC has also been considered as one of the protective strategies against spinal cord ischemia.…”
mentioning
confidence: 99%